A Contrastive Analysis of Liwc and Rhetorical Devices in Airlines’ Advertisements for Frequent Flyer Programs - Mongkolchai Tiansoodeenon,; Wongpunya, Wannipa; Warunsiri Pornpottanamas, (Journal of Contemporary Social Sciences and Humanities, 2025)
This study employs text analysis to investigate and compare the use of Aristotelian rhetorical (ethos, logos, and pathos) and Linguistic Inquiry and Word Count (LIWC) categorized into four language variables: clout, analytical thinking, authenticity, and emotional tone in frequent flyer program (FFP) advertisement between the full-service and low-cost airlines on the Skytrax website. The population consists of 100 airlines recognized as the world’s best in 2023. A purposive sampling technique was used to reduce the number of airlines to thirty-six which was then divided into two groups: eighteen full-service airlines and eighteen low-cost airlines. The Aristotelian rhetorical devices and the LIWC program were used as research instruments. To analyze the data, percentages were used, and the item objective congruence (IOC) score rating from three doctoral-degree holders in linguistics was implemented to ensure reliability. The findings reveal that ull-service airlines placed emphasis on pathos, ethos, and logos, respectively, while low-cost airlines highlighted logos, pathos, and ethos, in a respective order. The results of the LIWC analysis show that the FFP advertisements of full-service airlines scored higher in clout, analytical thinking, and authenticity than those of low-cost airlines. However, both types of airlines scored equally in terms of emotional tone. Full-service airlines employed more formal and logical language to establish an exclusive experience and inspire confidence, while low-cost airlines favored straightforward and easily comprehensible sentence structures to foster a sense of opportunity in passengers who might want to participate in their FFP programs.